Kajian Validitas Berbagai Metode Hidrograf Satuan Sintetik Dalam Aplikasinya Untuk Daerah Aliran Sungai Tak Terukur - Ariani Budi Safarina (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2012)
In This study is had analyzed thirteen watersheds on the island of Java with wide ranges from 22 km2 to 2666 km2. Watershed characteristics as indicators are the area, the length of main rivers and the shape of the watershed. The Convolution method is used to determine the observation unit hydrograph using rainfall and water level data from automatic stations. This unit hydrograph is compared with four synthetic unit hydrograph methods namely Snyder, SCS, Nakayasu and Gama-1, using the comparison parameters of hydrograph shape and also hydrograph parameters i.e. peak discharge, peak time and time base. The results showed that the method of Snyder, SCS, Nakayasu and Gama-1 have an average deviation of hydrograph shape and peak discharge Qp, consecutive 21% and 36%, 116% and 185%, 17% and 4%, 32% and 24%. Three methods, Snyder, SCS and Nakayasu show direct runoff volume equal to one mm, except the method of Gama-1, so that it has to be corrected to conform with the basic principles of unit hydrograph. Based on the result of this research, it is concluded that the Nakayasu method is more appropriate for watersheds having wide range characteristics.